Acetazolamide-responsive Episodic Ataxia Without Baseline Deficits or Seizures Secondary to GLUT1 Deficiency: A Case Report and Review of the Literature. Issue 1 (January 2018) - Tchapyjnikov, Dmitry; Mikati, Mohamad A.
Abstract : Introduction: Glucose transporter type 1 deficiency syndrome (GLUT1 DS) is caused by impaired glucose transport across the blood-brain barrier and commonly presents as severe early onset epilepsy, developmental delay, and movement abnormalities. In rare instances, GLUT1 DS can present as a paroxysmal movement disorder without the other classic symptoms. Episodic ataxia (EA) secondary to GLUT1 DS has been previously reported, but all previous patients had seizures and/or baseline abnormalities on neurological examination. Isolated acetazolamide-responsive EA secondary to GLUT1 DS without deficits on neurological examination and without seizures has not been described. Case Report: A 4-year-old boy presented with EA, no baseline neurological abnormalities, and no history of seizures. He was initiated on acetazolamide with a ≥75% improvement in frequency and severity of episodes. A genetic testing panel for EAs subsequently returned positive for a mutation in the SLC2A1 gene and cerebrospinal fluid analysis showed hypoglycorrhachia in the setting of normal blood glucose, which confirmed the diagnosis of GLUT1 DS. His symptoms resolved completely with ketogenic diet initiation even with discontinuation of acetazolamide. Conclusions: To our knowledge, this represents one of the mildest described presentations of nonepileptic GLUT1 DS consisting of acetazolamide-responsive EA without seizures or baseline neurological examination abnormalities. Our experience supports increased vigilance for this treatable cause of EA.